Hubungan Pengetahuan Keluarga dan Perilaku Keluarga pada Penanganan Awal Kejadian Stroke - Marina T. N Rosmary; Fitria Handayani (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2020)
Introduction: Early intervention of stroke would be reduced mortality and risk of disability. Early intervention was supported by the knowledge of risk factors and early symptoms of stroke. This study was aimed to determine the relationship between family knowledge and behavior in the initial treatment of stroke events. Methods: This study used a correlational descriptive design with cross-sectional approach. The researchers employed a non-probability sampling i.e. accidental sampling. The study was conducted at a hospital in Semarang in May 2019. The respondents were 77 families of patients during the stroke. The knowledge tool used the Stroke Recognition Questionnaire (SRQ) consisting of 30 questions and a behavioral questionnaire involving nine questions. Data analysis used Spearman Rank. Results: The result of bivariate analysis indicates there is a correlation between family knowledge and behavior with the value P = 0.000 and r = 0.83. Conclusion: The study concluded there was a correlation between knowledge and behavior. Correlation between the two variables was strong and indicated the positive direction of correlation which the higher of knowledge influenced the better of Family behavior. Nursing interventions needs to be developed to increase knowledge about the risk factors and early symptoms of stroke and management at home at the stroke outbreak.